A model for e-commerce adoption by small and medium-sized enterprises in Algeria - Hassen, Houache (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2021)
Small and Medium-sized Enterprises (SMEs) are regarded as the backbone of the growth of the world economy. They had recently experienced rapid growth and improved their business activities in terms of customer numbers and revenue expansion when they began using e-commerce in their business. Although there is a growing interest in e-commerce, its use is still insufficient in Algeria. SMEs show a little acceptance of e-commerce in their business processes. Consequently, e-commerce has not yet found its place in Algeria, since it has not achieved the desired start as an approved means of trade. The main objective of this study is to identify the direct, indirect and mediating factors that have prevented SMEs from adopting e-commerce in Algeria and develop a model to be adopted. To obtain a clear vision on the subject of adopting e-commerce in Algeria, a preliminary study was established with semi-structured interviews that were conducted with 7 SME managers. Then, the conceptual model was developed through the models and theories which are among the most frequently applied theoretical models on the adoption of e-commerce in developing countries. These models are Unified Theory of Acceptance and Use of Technology (UTAUT), Technology Organisation Environment (TOE), and Perceived eReadiness Model (PERM) as well as from the results of the preliminary study. This research uses the quantitative research method, where a survey responded by 315 SMEs in Algeria. The research hypotheses were examined, and the proposed research model was validated through Structural Equation Modelling (SEM) using AMOS software. The main findings of the present study comprise some key factors that have a significant effect on e-commerce adoption which are competitive pressure, delivery systems, necessary guidance and assistance, buying habits, enterprise financial resource, human resources, and trust in the state system and IT skills. The significant effects were mediated by three variables which are awareness, fear of risk in e-commerce, and the intention to adopt e-commerce. At the same time, there are three non-significant factors which are government e-readiness, bank e-readiness and technology resources. Besides, the measures of goodness-of-fit indices GOFI indicate that the conceptual model revised is a fit model for e-commerce adoption by SMEs in Algeria. This model would be provided useful information for SMEs, policymakers, and academics.